KONTEKSTUALISASI FIQH (PEMBACAAN PEMIKIR ISLAM KH. MA. SAHAL MAHFUDH) - Ahmad Faisal (TAHKIM, 2017)
During this religious study is dominated by the theocentric tendency. Consequently, in the social context, the teaching of law as stipulated in fiqh, often seen not in line with the practical lifeforms. It is caused by overly formalistic view of fiqh. Therefore in accordance with the nature andprocess of ijtihad, so the change of perspective jurisprudence toward fiqh to be more realistic and dinamic, it possible and necessary. Thus, fiqh can be optimazed and actualized as the values and behaviors in the evolving social life. If it is not done, so the possibility of futurejurisprudence will only be reference in any aspect ubudiyah or remembered as the legaly of civilization in the field of thought. By Kiai Sahal, must have the courage to change the paradigmof paradigms in fiqih “ortodoxy truth” to the paradigm of “social meaning”, if the first subjecting reality to the truth of fiqh and character black and white “in meaning reality, the later using fiqhas “counter discourses” and with showing his character style. Keyword: contestuality, social fiqh.